Karyotype analysis in Saraca asoca (Roxb.) de Wilde - Deepa, K.S.; Santoshkumar, A.V.; Rekha, K; Joseph, Jiji (Journal of Tropical Agriculture, 2013)
A study on karyomorphological analysis in Saraca asoca was carried out in College of Forestry, Thrissur, Kerala. The study revealed the presence of 34 chromosomes in the somatic cells of Saraca asoca for the first time, in contrast to the earlier report of 2n = 24. Pre-treating with 8-hydroxyquinoline and fixing it in Carnoys II and using the stain acetocarmine gave the best cytological preparation .